1991
DOI: 10.1111/j.1445-2197.1991.tb00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Open Management of Septic Abdomen by Marlex Mesh Zipper

Abstract: Marlex mesh with zipper was used for abdominal closure in 5 of 147 patients with generalized peritonitis seen during a period of 2 years. Residual/recurrent intra‐abdominal sepsis necessitating repeated explorations prompted use of this technique followed by frequent peritoneal lavages. Abdominal sepsis was successfully controlled in 4 of 5 patients, although we lost 3 of 5 patients due to multiple factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 5 publications
0
13
0
1
Order By: Relevance
“…Eight series described peritonitis patients only [6, 7, 12, 19, 20, 35, 45, 54], and three described vascular patients only [16, 18, 42]. The remaining 11 series described general surgical, peritonitis, pancreatitis, and vascular patients [1, 3, 4, 18, 21, 30, 31, 41, 46, 52, 53].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight series described peritonitis patients only [6, 7, 12, 19, 20, 35, 45, 54], and three described vascular patients only [16, 18, 42]. The remaining 11 series described general surgical, peritonitis, pancreatitis, and vascular patients [1, 3, 4, 18, 21, 30, 31, 41, 46, 52, 53].…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen series described meshes or sheets (Table 4) [8, 9, 11, 16, 23, 27, 32, 35, 36, 39, 42, 43, 49, 50, 54, 55]. Zippers were used in seven series (Table 4) [4, 6, 19, 30, 31, 45, 52]. The silo was used in three series [2, 7, 11], and skin only in two series [9, 11].…”
Section: Resultsmentioning
confidence: 99%
“…After the literature review, 12 articles were selected 16,[18][19][20][21][22][23][24][25][26][27][28] (Table 2).…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…The use of the zipper allows regular cleansing of the peritoneal cavity, gentle lysis of adhesions to permit access to loculations, and early detection and management of complications. Reports from other institutions in the literature worldwide have shown that the use of zippers facilitated reexploration, reducing operative time and allowing the performance of the procedure in the intensive care unit 1,10,12,14. The experience in our institution in the use of abdominal zippers for abdominal wall closure has been limited to the management of peripancreatic sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported on the use of abdominal zippers, including Stone and Strom in 1984,13 who demonstrated the advantages of utilizing zipper closure of the abdomen in gross peripancreatic sepsis treated by sequential laparotomy. Others have encouraged zipper use, not only in severe intraabdominal infections but also in patients with questionable bowel viability, and for damage control in trauma 5,14,15…”
Section: Introductionmentioning
confidence: 99%